Effects of starch nanoparticle-stabilized oleic acid emulsions and warm storage on the structural properties and starch digestibility of cooked rice - Ah-In Kim; Jae Young Park; Hyun Ho Bae; Sang Min Cha; Jong-Yea Kim; Ju Hun Lee; Eun Young Park; Hyun-Jung Chung (Food Research International, 2026)

Ferroptosis modulation by Toxoplasma gondii suppresses sodium iodate–driven age-related macular degeneration - Xin-Cheng Wang; Guan-Hao Hong; Yu-Sun Yun; In-Wook Choi; Jaemin Yuk; Guang-Ho Cha (Genes & Genomics, 2026)

Polymer semiconductor-coated 3D bilayer cellulose nanofiber/polydimethylsiloxane aerogel for enhanced solar-driven interfacial water evaporation - Keerthnasre Dhandapani; Gayoung Ham; Hossein Fattahimoghaddam; In Ho Kim; Hyojung Cha; Xiaowu Tang; Da Wan Kim; Tae Kyu An; Yong Jin Jeong (Desalination, 2025)

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

Establishment of a human induced pluripotent stem cell derived alveolar organoid for toxicity assessment - Jooyeon Lee; Hyosin Baek; Jimin Jang; Jaehyun Park; Sang-Ryul Cha; Seok-Ho Hong; Jieun Kim; Jong-Hee Lee; In-Sun Hong; Seung-Jun Wang; Ji Young Lee; Myung Ha Song; et al. (Toxicology in Vitro, 2023)

Changes in soil properties for 6 years of using the freshwater snail (Ampullaria tischbeini Dohrn) in a reclaimed sodic soil - Jong-Song Jo; Song-Ho Pak; Chol-Ho Ri; Song-Ok Cha; Gwang-Rim Kim; Chon-Il Ri; In-Song Kim (Journal of Soils and Sediments, 2020)

Paenibacillus lutimineralis sp. nov., Isolated From Bentonite - Eui-Sang Cho; In-Tae Cha; Dong-Ho Seo; Young-Do Nam; Seong Woon Roh; Jae-Hwan Kim; Myung-Ji Seo (Current Microbiology, 2019)

Pathogenic significance of hemorrhagic pneumonia in hematologic malignancy patients with Stenotrophomonas maltophilia bacteremia: clinical and microbiological analysis - Si-Ho Kim; Min Kyeong Cha; Cheol-In Kang; Jae-Hoon Ko; Kyungmin Huh; Sun Young Cho; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Effects of three-dimensional spheroid culture on equine mesenchymal stem cell plasticity - Mi Jeong Park; Jienny Lee; Jeong Su Byeon; Da-Un Jeong; Na-Yeon Gu; In-Soo Cho; Sang-Ho Cha (Veterinary Research Communications, 2018)

Expression and characterization of glutamate decarboxylase from Lactobacillus brevis HYE1 isolated from kimchi - Hee Seon Lim; Dong-Ho Seo; In-Tae Cha; Hyunjin Lee; Young-Do Nam; Myung-Ji Seo (World Journal of Microbiology and Biotechnology, 2018)

Chondrogenic potential and anti-senescence effect of hypoxia on canine adipose mesenchymal stem cells - Jienny Lee; Jeong Su Byeon; Keum Sil Lee; Na-Yeon Gu; Gyeong Been Lee; Hee-Ryang Kim; In-Soo Cho; Sang-Ho Cha (Veterinary Research Communications, 2016)

Unveiling abundance and distribution of planktonic B acteria and A rchaea in a polynya in A mundsen S ea, A ntarctica - Jong‐Geol Kim; Soo‐Je Park; Zhe‐Xue Quan; Man‐Young Jung; In‐Tae Cha; So‐Jeong Kim; Kyoung‐Ho Kim; Eun‐Jin Yang; Young‐Nam Kim; Sang‐Hoon Lee; Sung‐Keun Rhee (Environmental Microbiology, 2014)
Summary Polynyas, areas of open water surrounded by sea ice, are sites of intense primary production and ecological hotspots in the A ntarctic O cean. This study determined the spatial variation in communities of prokaryotes in a polynya in the A mundsen S ea using 454 pyrosequencing technology, and the results were compared with biotic and abiotic environmental factors. The bacterial abundance was correlated with that of phytoplankton, P haeocystis spp. and diatoms. A cluster analysis indicated that the bacterial communities in the surface waters of the polynya were distinct from those under the sea ice. Overall, two bacterial clades, P olaribacter (20–64%) and uncultivated O ceanospirillaceae (7–34%), dominated the surface water in the polynya while the P elagibacter clade was abundant at all depths (7–42%). The archaeal communities were not as diverse as the bacterial communities in the polynya, and marine group I was dominant (> 80%). Canonical correspondence analysis indicated that the oceanographic properties facilitated the development of distinct prokaryotic assemblages in the polynya. This analysis of the diversity and composition of the psychrophilic prokaryotes associated with high phytoplankton production provides new insights into the roles of prokaryotes in biogeochemical cycles in high‐latitude polynyas.

The combined effects of transforming growth factor-β and basic fibroblast growth factor on the human degenerated nucleus pulposus cells in monolayer culture - Erxing He; Ji Hao Cui; Chuang Li; Cheng Tang; In-Sung Kim; Young-Woo Kim; Ho-Guen Chang; Jae-Ryong Cha; Oh-Jong Byung; Yong-Chan Kim (Tissue Engineering and Regenerative Medicine, 2013)

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study - Sang-Ah Han; Sung-Won Kim; Eunyoung Kang; Sue K. Park; Sei-Hyun Ahn; Min Hyuk Lee; Seok-Jin Nam; Wonshik Han; Young Tae Bae; Hyun-Ah Kim; Young Up Cho; Myung Chul Chang; et al. (Familial Cancer, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Capsaicin-induced apoptosis in the human glioblastoma U87MG cells via p-38 MAPK and Bcl-2/Bax signaling pathway - Jin Ho Jeon; Yoon Ji Choi; In Ho Han; Byung Kwan Choi; Seung Heon Cha; Won Ho Cho (Molecular & Cellular Toxicology, 2012)

A method for detecting significant genomic regions associated with oral squamous cell carcinoma using aCGH - Ki-Yeol Kim; Jin Kim; Hyung Jun Kim; Woong Nam; In-Ho Cha (Medical & Biological Engineering & Computing, 2010)

Decolorization of triphenylmethane and azo dyes by Citrobacter sp. - Sun-Young An; Sang-Ki Min; In-Ho Cha; Yong-Lark Choi; Young-Su Cho; Cherol-Ho Kim; Young-Choon Lee (Biotechnology Letters, 2002)